Pengaruh Penambahan Puree Buah Nangka (Artocarpus heterophyllus Lamk.) Terhadap Karakteristik Permen Karamel Susu - Anggraeni, Vina Prilatmi; Timur Ina, Putu; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
Milk caramel candy is a confectionary product made from milk, sugar, glucose syrup, and fat. This research was aimed for determining the effect of jackfruit puree addition on the characteristics of milk caramel candy and ascertained the addition of jackfruit puree to produce the best characteristic of milk caramel candy. The research based on a Completely randomized design (CRD) containing 5 levels jackfruit puree addition, namely 0%; 5%; 10%; 15% and 20%. Each treatment was replicated 3 times to obtain 15 experimental units. Data was analyzed using analysis of variance and if the treatment had a significant effect, its followed by the Duncan multiple range test (DMRT). The results showed that the addition of jackfruit puree had a significant effect to moisture content, ash content, reducing of sugar, crude fiber, the value of L*, a*, b*, colour, flavor, texture, taste and overall acceptance (hedonic) and taste (skoring). The addition of 15% jackfruit puree for producing milk caramel candy the best characteristics with moisture content 7.29%, ash content 1.65%, reducing sugar 16.26%, total sugar 66.36%, sucrose content 47.59%, crude fiber 3.75%, value of L* 57.20, value of a* 17.17, value of b* 49.30. Colour, flavor, texture, overall acceptance is liked and taste strong and liked.